2017
DOI: 10.1002/phar.1892
|View full text |Cite
|
Sign up to set email alerts
|

β‐Lactam Therapy for Methicillin‐Susceptible Staphylococcus aureus Bacteremia: A Comparative Review of Cefazolin versus Antistaphylococcal Penicillins

Abstract: Methicillin-susceptible Staphylococcus aureus (MSSA) bacteremia is associated with high morbidity and mortality. Traditionally, antistaphylococcal penicillins (ASPs) have been considered the agents of choice for the treatment of MSSA bacteremia. Vancomycin has been demonstrated to have poorer outcomes in several studies and is only recommended for patients with severe penicillin allergies. Although cefazolin is considered as an alternative to the ASPs for patients with nonsevere penicillin allergies, cefazolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 45 publications
0
29
0
1
Order By: Relevance
“…using a PubMed database search (January 1996 to June 2016) stated that most of the reports of clinical failure with cefazolin are case reports or case series and that the clinical relevance of the cefazolin InE is not entirely clear, especially as susceptibility testing in clinical microbiology laboratories uses a standardized inoculum (8). This review states that, in addition, limited by small sample size and possible selection bias, the only comparative study to date examining the clinical impact of the cefazolin InE (i.e., the study referred to above from Asia [South Korea] [7]) did not show any significant differences in outcomes when comparing isolates with and without cefazolin InE.…”
mentioning
confidence: 99%
“…using a PubMed database search (January 1996 to June 2016) stated that most of the reports of clinical failure with cefazolin are case reports or case series and that the clinical relevance of the cefazolin InE is not entirely clear, especially as susceptibility testing in clinical microbiology laboratories uses a standardized inoculum (8). This review states that, in addition, limited by small sample size and possible selection bias, the only comparative study to date examining the clinical impact of the cefazolin InE (i.e., the study referred to above from Asia [South Korea] [7]) did not show any significant differences in outcomes when comparing isolates with and without cefazolin InE.…”
mentioning
confidence: 99%
“…Others have even suggested a treatment benefit with cefazolin over antistaphylococcal penicillins [17, 24]. Several comprehensive reviews of these data have been published elsewhere [12, 25, 26]. Limitations of previous studies include small patient populations, retrospective study design, and lack of adverse effect analyses.…”
Section: Discussionmentioning
confidence: 88%
“…The findings from this systematic review suggest that treatment with cefazolin in adults is associated with a clinically important favorable safety profile compared to antistaphylococcal penicillins because of lower risks of nephrotoxicity, acute interstitial nephritis, hepatotoxicity, hypersensitivity reactions, and discontinuation due to ADRs. In other studies, cefazolin has demonstrated at least equivalent efficacy compared to antistaphylococcal penicillins (26) and improved cost-effectiveness (14). Therefore, cefazolin should be considered a first-line treatment option for MSSA bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent large multicenter retrospective cohort study by Mc-Danel et al (29) showed a significantly lower mortality risk with cefazolin than with nafcillin or oxacillin. If this difference in mortality is true, it is possibly due to antibioticrelated ADRs and the associated antibiotic discontinuation rates in light of findings from more-recent studies that suggest equivalent efficacies of cefazolin and antistaphylococcal penicillins (26).…”
Section: Discussionmentioning
confidence: 99%